Thermal energy development in magnetohydrodynamic flow utilizing titanium dioxide, copper oxide and aluminum oxide nanoparticles: Thermal dispersion and heat generating formularization - Bilal Hafeez, Muhammad; Krawczuk, Marek; Jamshed, Wasim; Tag El Din, El Sayed M.; El-Wahed Khalifa, Hamiden Abd; Aziz ElSeabee, Fayza Abdel (Frontiers in energy research, 2022)
Background: The main aim of this article heat transfer in thermal engineering deals with the production, use, transformation, and transfer of thermal energy. Engineering and industrial fields including food packaging, the production of food additives, electronic cooling, microturbines, etc. Heavily rely on heat transmission. Due to its intriguing potential in industries like the production of polymers, paper, crystal glass, etc., scientists from all over the world have endeavored to investigate the effect of heat transmission on fluid flows past an expandable surface. Purpose: The use of a single-phase technique to assess Newtonian nanofluid flow along stretched surfaces with heat transfer convective models is emphasized in this research. A mathematical formulation is used to do the numerical computations for copper oxide (CuO), aluminum oxide (Al 2 O 3 ), and titanium dioxide (TiO 2 ) nanoparticles using water (H 2 O) as the base fluid. Formulation: The fifth-order Runge-Kutta shooting method procedure with shelling performance are used to solve non-linear ordinary differential equations with boundary conditions numerically. Researched and analyzed for changes in several parameters, plots illustrating the effects of motivated and non-motivated MHD are given to explain the physical values. Finding: Dispersion of solid items in the working fluid is reported to significantly improve thermal performance. The Biot number determines how convective the border is. With an increase in the Biot number, the fluid’s temperature drops significantly. It has been demonstrated that Copper oxide (CuO), nanoparticles are more efficient than Titanium Dioxide (TiO 2 ) and Aluminum Oxide for thermal enhancement (Al 2 O 3 ). Novelty: As far as the authors are aware, no studies have been done on the steady MHD flow and convective heat transfer of nanofluids over a nonuniform stretched surface under the influence of a heat source and viscous dissipation.